Kinetic Studies of Platelet Aggregation Induced by Adenosine Diphosphate and Its Inhibition by Chelating Agents, Guanidino Compounds, and Adenosine - Skoza, L; Zucker, Marjorie B; Jerushalmy, Z; Grant, R (Thrombosis and Haemostasis, 1967)
The kinetics, activation, pH dependence and inhibition of platelet aggregation induced by ADP were studied by recording the OD of stirred PRP from blood anticoagulated with acid-citrate-dextrose solution. There was a lag period between the addition of ADP and the initiation of aggregation. Addition of ADP in the absence of stirring or ionized calcium did not cause aggregation. When aggregation was subsequently initiated by stirring or the addition of CaCl2 there was no lag period. The steepest slope of the OD curve was used as the reaction velocity (V). It was affected by the concentration of calcium ions and was maximum at pH 8.0. When the ADP concentration was varied in the presence of different concentrations of ionized calcium, the overall kinetics revealed a series of rectangular hyperbola segments which did not pass through the origin. These observations led to the conclusion that the overall reaction can be depicted as a chain reaction: ADP interacts reversibly with platelets; when calcium is present these platelets become “sticky” and, when stirred, they aggregate. Kinetic studies of inhibition indicated that adenosine is a competitive inhibitor of ADP. The guanidino compounds tested were noncompetitive with respect to ADP but their inhibitory activity was counteracted by calcium.